Analisa Rasio Keuangan untuk Memprediksi Perubahan Laba pada Perusahaan Telekomunikasi Indonesia - Engelwati Gani; Almitra Indira (Bina Nusantara University, 2011)
This study was conducted to test the variable Current Ratio (CR), Net Profit Margin (NPM), Operating Margin Ratio (OMR), Return On Equity (ROE), Return on Assets (ROA) and Total Asset Turn Over (tattoo) to changing profit. Data obtained by the method of purposive sampling criteria (1) Telecommunications Companies listed on the Indonesia Stock Exchange (IDX) and consistently throughout the study period (2003 to 2010) and Telecommunication Company that provides the data of financial statements during the study period (2003 to 2010). The analysis showed that the data used in this study have been normally distributed and satisfy the classical assumptions, which include: there is no autocorrelation, no symptoms of multicollinearity, and no symptoms hetereskedasitas. From the results of regression analysis showed that the variables Net Profit Margin (NPM) and Operating Margin Ratio (OMR) partially significant effect on change in earnings. While the variable Current Ratio (CR), Return on Equity (ROE), Return on Assets (ROA) and Total Asset Turn Over (TATTOO) no significant effect on changes in earnings. The six variables used in the study jointly affect changes in earnings. Predictive capability of the six variables simultaneously is equal to 36.4%.